Pengaruh Keselamatan Konstruksi terhadap Produktivitas Kerja pada Pemasangan Erection Grider di Proyek Pembangunan Jalan Tol - Zanuar Ilham Mahendra; Ferida Yuamita (Jurnal Kendali Teknik dan Sains, 2026)
PT Adhi Karya (Persero) Tbk is a State-Owned Enterprise (BUMN) in Indonesia that operates in the construction industry. PT. Adhi Karya (Persero) Tbk. was awarded the contract for the Yogyakarta-Bawen toll road construction project, Package 1, Section 1. Construction safety is a very important aspect in the project. The toll road construction project involves work at heights, especially on erection grider work. Erection grider work is a high-risk job, so construction safety must be guaranteed. If construction safety is not guaranteed in the work environment, workers will be more careful in working to reduce risks so that work slows down. This can reduce work productivity. However, when safety is guaranteed, workers will feel safe to work so that it can increase work productivity. This study aims to determine the effect of construction safety (X) on work productivity (Y). The data collection method was carried out by distributing questionnaires to 30 respondents of erection grider workers. Data processing used the Structural Equation Modeling–Partial Least Squares (SEM PLS) method with SmartPLS 4.0 software. The results of data processing showed that construction safety had a significant influence on work productivity with a t-statistic value of 7.329 and a p-value of 0.000.